Care for post-COVID-19 condition in Germany from the perspectives of patients, informal caregivers and general practitioners: Study protocol for a mixed methods study. - Melanie Brinkmann; Maike Stolz; Annika Herr; Christoph Herrmann-Lingen; Imke Koch; Christiane Müller; Frank Müller; Uta Sekanina; Jona Theodor Stahmeyer; Martina de Zwaan; Christian Krauth; Nils Schneider (PLoS ONE)
Background A large number of individuals suffer from post-COVID-19 condition (PCC), characterised by persistent symptoms following a SARS-CoV-2 infection with an impact on daily personal and professional activities. This study aims at examining which (health) care services are used by PCC patients in the German federal state of Lower Saxony, and how these patients manage their condition. The perspectives of patients, informal caregivers and general practitioners (GPs) will be considered. Methods The study will employ a mixed methods design. Patients' perspective will be evaluated through an online survey of: (1) 21,000 adult individuals with a PCC diagnosis (ICD10 U09.9!) in their statutory health insurance claims data in 2022 ("AOK survey") and (2) a self-selected sample of adult individuals with a proven SARS-CoV-2 infection in 2023 and persistent symptoms ("public survey"). Additional data sources will be claims data (n = 27,275) and 25-30 semi-structured interviews. Informal caregivers' perspective will be collected through an online survey and semi-structured interviews. GPs' perspective will be evaluated through four focus groups involving six to eight participants each and an online survey of all registered and practicing GPs in Lower Saxony (approximately 5,000). All survey data will be descriptively analysed. In addition, correlation analyses and multivariable regression analyses will be conducted, for example on factors influencing affected individuals' use of medical services. Interview and focus group data will be subjected to qualitative content analysis. A health economic analysis will be used to determine the costs of PCC to health care payers, patients and society. The project will conclude with an expert workshop to discuss the results and derive recommendations. Discussion The results of the study will provide a multidimensional description of the (health) care situation and needs of patients with PCC, and derive recommendations for improving health care. Trial registration The VePoKaP study is registered at the German Clinical Trials Register (DRKS00032846).